Cannibalizing the Wiindigo: The Wiindigog in Anishinaabeg and Oji-Cree Boreal Landscapes and Its Re-presentations in Popular Culture - Agnieszka Pawłowska-Mainville (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
This paper will discuss the Wiindigo, a cannibalistic character among some Indigenous peoples of North America. Illustrated through the Anishinaabeg and Oji-Cree, two Algonquin-speaking Indigenous groups, the Wiindigo serves as a personification of fear and hunger, and alludes to the cultural heritage elements of the boreal forest food system as well as the differing legal systems in Canada. In examining the Wiindigo from the Indigenous cultural and historical perspectives related to the author by several knowledge-holders, as well as from EuroCanadian popular culture representations, the paper illustrates the importance of the Wiindigo to Anishinaabe and Oji-Cree world views, customary governance, and contemporary lived experience.